(untitled) (Desenvolvimento em Questão, 2020)
The objective of this article is to present studies carried out in the territory of the Autonomous Community of Castilla-La Mancha (Spain), in order to investigate strategies of development based on the concept of agrarian heritage, and subsequently consider the agrarian assets of the region of Contestado (Brazil), with a view to the establishment of similar strategies of regional development. The methodological approach considered the examination of the plans for the development of Castilla-La Mancha, based on fieldwork carried out in the provinces of that Spanish territory and supported in the review of literature on the conceptual category of agrarian heritage. It is concluded that the search for strategies of regional development can be based on similar actions carried out in other territories and that their implementation will require the mobilization of the social and political agents of the micro-region of Canoinhas.